Impact of Ferti‐Irrigation with Vinasse on Groundwater Quality1. (18th September 2014) - González, Luis; Mejía, Miguel
Abstract Vinasse, a residual substance left after sugarcane alcohol distillation, is a mixture of water and organic compounds and can be used as a substitute for chemical fertilizers. Some alcohol industries in Mexico have adopted its utilization in the irrigation of sugarcane plantations. If vinasse percolates and reaches the groundwater, microbial degradation of the organic matter produces a sequence of redox reactions in which O2, NO3‐, Mn (IV), Fe (III), SO42‐ and CO2 are reduced. This causes problems with groundwater quality, because manganese and iron become soluble, causing the water to acquire a brown colour and bad taste. The aim of this study was determine the effect of ferti‐irrigation with vinasse over 50 years in the groundwater quality of an aquifer in east central Mexico. The results shows a shallow groundwater table (14 m) in the area where vinasse is used. The results also show reduction of oxygen, nitrate reduction and manganese reduction where vinasse is used for ferti‐irrigation. In fact, some wells exceed the maximum permissible limit for manganese established by Mexican standards. The primary cause of groundwater contamination is attributed to the dissolution of the manganese present in the soil, during the oxidation of organic matter introduced to the aquifer by deep percolation of irrigation water with vinasse. Copyright © 2014 John Wiley & Sons, Ltd.